P673 In-vitro activity of SMT-571 and comparators against clinical isolates and reference strains of neisseria gonorrhoeae. (14th July 2019) - Meo, Paul; Mason, Clive; Khan, Nawaz; Unemo, Magnus; Jacobsson, Susanne
Abstract : Background: The emergence and spread of multidrug resistance to antibiotics used to treat gonorrhoea has resulted in a dramatic loss of effective regimens for the condition. Currently, the extended spectrum cephalosporin, ceftriaxone, is the only viable monotherapy option available, however, resistance to this last line treatment is now emerging globally. Herein, we assessed the in vitro activity of a novel small molecule antimicrobial with a new mechanism of action, SMT-571, against a large collection of N. gonorrhoeae clinical isolates and reference strains including numerous MDR and XDR gonococcal isolates. Methods: MICs (mg/L) of SMT-571 were determined by agar dilution according to current CLSI guidelines. The MICs of ceftriaxone, cefixime, azithromycin, ciprofloxacin, spectinomycin, tetracycline, and ampicillin were determined using the Etest method (AB bioMérieux, Marcy l'Etoile, France). Results: SMT-571 showed potent in vitro activity against all the tested N. gonorrhoeae isolates (n=262) with MICs ranging from 0.064 to 0.125 mg/L, and the MIC50, MIC90 and modal MIC were all 0.125 mg/L. The compound was not influenced by pre-existing resistance mechanisms with no cross-resistance or correlation between the MICs of SMT-571 and comparator agents being observed. Conclusion: This study is the first broad evaluation of the in vitro activities of a new mechanism, novel small molecule antimicrobial for the treatment of gonorrhoea. SMT-571 demonstrated high in vitro activity against a large geographically, temporally and genetically diverse collection of clinical N. gonorrhoeae isolates and international reference strains, including various types of high-level resistant, MDR and XDR gonococcal isolates. Disclosure: No significant relationships.